STATUS HUKUM DARAH REPRODUKSI PEREMPUAN (ANALISIS INTEGRATIF ANTARA PENDEKATAN NORMATIF DAN KEDOKTERAN TERHADAP KETIDAKTERATURAN MENSTRUASI PADA AKSEPTOR KB) - Wahyu Setiawan (Universitas Islam Negeri Fatmawati Sukarno, 2015)
One of the effects of hormonal contraceptive in family planning (KB) acceptors is the irregularity of the menstrual cycle. Changes in menstrual patterns due to progesterone contraceptive system generally in the form of change and cycle time, and spoting events (incidence of blood spots are irregular and sometimes prolonged). These changes can occur over 15 days. So that raises a problem of provision between menstrual blood status (haidh) or istihâdhah. The purpose of this article is to discuss the reality of the menstrual cycle changes for acceptors of family planning (KB) and trying to find legal status of reproductive blood as applicable legal product. This articles hows that the incidence of spoting should be seen in terms of the timing of the spoting. If bleeding occurs before menstrual blood every month, it is not judged as menstruation but istihâdhah. If spoting occurs after normal bleeding, then see the normal number of days of bleeding and spoting itself. If spoting events that accompany normal bleeding exceeds fifteen days, then spotting after fifteen days specified as istihâdhah